2020
DOI: 10.1002/jtr.2412
|View full text |Cite
|
Sign up to set email alerts
|

Senior's travel constraint, negotiation strategy and travel intention: Examining the role of social support

Abstract: This paper explores how travel constraints influence seniors' travel decision. By including social support for travel as a moderator in the hierarchical constraint model, we examined the effects of travel constraints, social support, and negotiation strategies on seniors' travel intentions. Face-to-face questionnaire interviews were conducted with Chinese seniors. The results were in accordance with the hierarchical constraint model in general, but also revealed some interesting findings: (a) for Chinese senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Despite these possible health concerns, about half of all respondents displayed the intention to visit or had a neutral attitude toward visiting, which indicates a similar attitude as those of respondents in Lee and Chen's [73] study on the low impact of a perceived health risk, the bird flu, and the Severe Acute Respiratory Syndrome on visit intention. The low intention to visit among "Indifferent Seniors" is not related to health risks but to other intrapersonal and interpersonal constraints or structural travel constraints, as listed by Chen et al [70], or an overall higher perceived financial risk due to the pandemic and worries about the future, similar to Le Serre et al [74].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Despite these possible health concerns, about half of all respondents displayed the intention to visit or had a neutral attitude toward visiting, which indicates a similar attitude as those of respondents in Lee and Chen's [73] study on the low impact of a perceived health risk, the bird flu, and the Severe Acute Respiratory Syndrome on visit intention. The low intention to visit among "Indifferent Seniors" is not related to health risks but to other intrapersonal and interpersonal constraints or structural travel constraints, as listed by Chen et al [70], or an overall higher perceived financial risk due to the pandemic and worries about the future, similar to Le Serre et al [74].…”
Section: Discussionmentioning
confidence: 84%
“…Travel constraints are defined as "barriers that inhibit people's ability to travel, decrease traveling time, and frequency or cause less satisfactory travel experiences" [70]. Among studies on travel constraints, researchers have paid special attention to the senior population [51,71,72].…”
Section: Travel Constraints Travel Worry Travel Fear and Perceived Ri...mentioning
confidence: 99%
See 1 more Smart Citation
“… Koronios et al (2020) concluded that intrapersonal constraints significantly influence consumption behaviors. Similarly, this type of constraints plays a powerful role in determining travel decision making ( Karl et al, 2020 ; Chen et al, 2021 ). However, Hawkins et al (1999) argue that intrapersonal constraints may not be a major factor causing non-participation in leisure activities, and Yang et al (2022) also found that intrapersonal constraints do not directly influence travel intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, it is found that prospective travelers’ intentions to travel will decrease under the negative impacts of structural constraints ( Lai et al, 2013 ; Wong and Kuo, 2021 ). Conversely, Khan et al (2019b) concluded that structural constraints have no significant relationship with travel intentions as Chen et al (2021) explained that structural constraints are negotiable. In the current context of the COVID-19 pandemic, structural constraints are arguably more salient and powerful ( Hall et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%